The role of banks in the transmission of monetary policy - Joe Peek; Eric S. Rosengren (Federal Reserve Bank of Boston, 2013)
The transmission of monetary policy, especially in light of recent events, has received increased attention, especially with respect to the efficacy of the bank lending channel. This paper summarizes the issues associated with isolating the bank lending channel and determining the extent to which it is operational. Evidence on the effectiveness of the bank lending channel is presented, both in the United States and abroad. The paper then provides observations about the likely consequences for the effectiveness of the lending channel of the changes in the financial environment associated with the recent financial crisis.
Keywords: E52; G21; 330; bank lending channel; loan supply; monetary policy; financial crisis; bank regulation; financial innovation